A parametric test evaluating smallholder farmers' training needs in Uganda: A case of dairy farmers in the Rwenzori region. Issue 3 (3rd September 2018) - Kataike, Joanita; Modekurti, Durga Prasad Venkata; Butali, Eric; Magumba, David; Mugenyi, Andrew Ronnie; Aine-Omucunguzi, Adalbert; Gellynck, Xavier
Abstract : Purpose: Effective rural agribusiness development requires dedicated training programmes therefore, this paper is an attempt to investigate smallholder farmers' TNs in the dairy agribusiness sector. The purpose of this paper is to study a bigger research project of the dairy value chain in agribusiness framework in the Rwenzori region. Design/methodology/approach: A sample size of 100 dairy farmers were randomly selected from two Districts in the Rwenzori region. The descriptive statistics (mean and standard deviation) provided a basis for discussion. Furthermore, parametric Pearson coefficient test was conducted to examine the smallholder farmers' TNs and assess its association with selected socio-demographic characteristics of the dairy farmers. Findings: The analysis indicated that dairy farmers expressed the need for a training program. Most frequently requested topics include: fodder cultivation, quality and safe milk handling, milk marketing, calf feeding and rearing, animal nutrition and financial literacy out of 12 topics. The least desired TNs was record keeping. Research limitations/implications: The findings contribute to the understanding of dairy farmers' TNs. Practical implications: The identified 12 key training intervention areas for the dairy farmers inform policymakers Dairy Development Authority and other development bodies in the Rwenzori region to address the challenges and improve smallholder dairy farming practices. Originality/value: The study applies a synthesis review to identify theoretically acceptable variables that measure smallholder farmers' TNs in the dairy agribusiness. The paper also shares the empirical evidence of a pioneering attempt to identify smallholder dairy farmers' TNs in Uganda.